2022
DOI: 10.3389/fendo.2022.922825
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cilia in Pancreatic β- and α-Cells: Time to Revisit the Role of Insulin-Degrading Enzyme

Abstract: The primary cilium is a narrow organelle located at the surface of the cell in contact with the extracellular environment. Once underappreciated, now is thought to efficiently sense external environmental cues and mediate cell-to-cell communication, because many receptors, ion channels, and signaling molecules are highly or differentially expressed in primary cilium. Rare genetic disorders that affect cilia integrity and function, such as Bardet-Biedl syndrome and Alström syndrome, have awoken interest in stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 223 publications
(315 reference statements)
0
0
0
Order By: Relevance
“…At a T2D signal on chromosome 11, risk variants increase the activity of a beta cell cRE linked to DEUP1 as well as DEUP1 expression in islets. DEUP1 is a component of cell division machinery 80 and, given in vitro evidence that DEUP1 can self-assemble 81 , increased DEUP1 activity and assembly may alter signal reception or microtubule dynamics 82 . Other genes linked to beta cell cREs affected by T2D risk variants include UBE2E2, which alters insulin secretion in mouse beta cells 83 , and CD101, which has no established role in beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…At a T2D signal on chromosome 11, risk variants increase the activity of a beta cell cRE linked to DEUP1 as well as DEUP1 expression in islets. DEUP1 is a component of cell division machinery 80 and, given in vitro evidence that DEUP1 can self-assemble 81 , increased DEUP1 activity and assembly may alter signal reception or microtubule dynamics 82 . Other genes linked to beta cell cREs affected by T2D risk variants include UBE2E2, which alters insulin secretion in mouse beta cells 83 , and CD101, which has no established role in beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…This pathological state alters the functional capacity of the pancreas and liver, contributing to the pathogenicity of T2DM [7,9,10]. In this line of evidence our group has made a substantial contribution to explain the role of IDE in α-cells on hyperglucagonemia [15,16], however this topic is out of the scope of this thesis.…”
Section: I2 Liver Glucagon Signaling and Hyperglucagonemia In T2dmmentioning
confidence: 91%
“…Another putative explanation for GCGR lost may be cytoskeleton disarrangement. Recently, we reported that genetic depletion of Ide in α-cells (αTC1.9 cell line transfected with an Ide-targeting siRNA) resulted in cytoskeleton disarrangement and a significant reduction in the number of primary cilia [15,16].…”
Section: V31 Hepatic Glucagon Signaling In Hepatocytesmentioning
confidence: 99%